Cabeça de Lenin: a reconstrução da história e a guerra por uma nova identidade ucraniana - Rocha, Yan Boechat (2024)
This study examines the transformation of Ukrainian national identity in the post-Soviet context, with emphasis on the second decade of the 21st century, marked by geopolitical tensions and direct confrontation between Ukraine and Russia. It focuses on the analysis of the removal of Lenin monuments, symbolizing Ukraine’s effort to distance itself from its Soviet heritage, and explores the emergence of a new collective identity intertwined with nationalist and pan-European ideals. Centering on a contextual analysis of recent events, interviews, and photographs collected and taken by the author on-site, this work seeks to reveal the complexities in the reconstruction of Ukrainian national identity. Special attention is given to the challenges faced by the Ukrainian government in rejecting a past of political stability under Soviet rule and in seeking closer ties with Europe, despite deep ethnic, religious, and cultural ties with Russia. Through the theoretical lens of Benedict Anderson’s “Imagined Communities,” (2018), we assess how memories and symbols are employed in creating a sense of unity and national distinction. The study focuses on key actors such as the Kiev government, nationalist movements, and civil society, to illustrate how different segments of the population participate in and react to this process of identity redefinition, highlighting the importance of a contextual and specific approach to understanding the dynamics of national identity in contemporary Ukraine